Answer:
The answer is 41
Step-by-step explanation:
(35 + 7) (6 - 5)
(42) × (1) = 41
Thus, The answer is 41
<u>-TheUnknownScientist</u>
Step-by-step explanation:
3, -12,7should be the correct answers
Answer:
The answer is A) y+4 =3(x+3)
Step-by-step explanation:
The slope is the rate of change, which you can see from the graph is m = 3/1 = 3.
Your options are given in point-slope form:
y-y1=m(x-x1)
Pick a point from the graph. I used;
(-3, -4). Now plug this into your point slope form equation.
y-(-4) = 3(x-(-3))
y+4=3(x+3)
-12 < -6x
-12/-6 > x divide both sides by -6
12/6 > x two negatives makes a positive
2 > x simplify
x < 2 switch sides
hope this helps, God bless!